Incorporating Pyrrolic and Pyridinic Nitrogen into a Porous Carbon made from C60 Molecules to Obtain Superior Energy Storage. Issue 8 (19th December 2016) - Tan, Ziqi; Ni, Kun; Chen, Guanxiong; Zeng, Wencong; Tao, Zhuchen; Ikram, Mujtaba; Zhang, Qiubo; Wang, Huijuan; Sun, Litao; Zhu, Xianjun; Wu, Xiaojun; Ji, Hengxing; et al.
Abstract : Nitrogen‐doped porous carbon is obtained by KOH activation of C60 in an ammonia atmosphere. As an anode for Li‐ion batteries, it shows a reversible capacity of up to ≈1900 mA h g −1 at 100 mA g −1 . Simulations suggest that the superior Li‐ion storage may be related to the curvature of the graphenes and the presence of pyrrolic/pyridinic group dopants.